2018
DOI: 10.3390/rs10030407
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Building Segmentation of Aerial Imagery Using Multi-Constraint Fully Convolutional Networks

Abstract: Automatic building segmentation from aerial imagery is an important and challenging task because of the variety of backgrounds, building textures and imaging conditions. Currently, research using variant types of fully convolutional networks (FCNs) has largely improved the performance of this task. However, pursuing more accurate segmentation results is still critical for further applications such as automatic mapping. In this study, a multi-constraint fully convolutional network (MC-FCN) model is proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(120 citation statements)
references
References 45 publications
0
103
0
Order By: Relevance
“…DeepResUnet adopted the U-Net as its basic structure and meanwhile took advantages of deep residual learning by replacing the plain neural units of the U-Net with the residual learning units to facilitate the training process of the network. Although some combined approaches of the U-Net with the deep residual network have been reported in recent studies [51,57,58], significant differences can be found between their network architectures and that of ours.…”
Section: About the Deepresunetmentioning
confidence: 60%
“…DeepResUnet adopted the U-Net as its basic structure and meanwhile took advantages of deep residual learning by replacing the plain neural units of the U-Net with the residual learning units to facilitate the training process of the network. Although some combined approaches of the U-Net with the deep residual network have been reported in recent studies [51,57,58], significant differences can be found between their network architectures and that of ours.…”
Section: About the Deepresunetmentioning
confidence: 60%
“…[25,26] trained FCNs to extract the buildings using the patch-wise method. In [27], Wu et al built a multi-constraint network to sharpen the boundaries of artificial object predictions. A trainable block, called the field-of-view (FoV), is proposed in [28] to boost the performance of the FCN.…”
mentioning
confidence: 99%
“…Facing this problem, we introduce Geoseg (https://github.com/ huster-wgm/geoseg), a computer vision package that is focus on implementing the state-of-the-art methods for automatic and accurate building segmentation and outline extraction. The Geoseg package implements more than 9 FCN-based models including FCNs [9], U-Net [10], SegNet [11], FPN [12], ResUNet [13], MC-FCN [14], and BR-Net [15]. For in-depth comparison, balanced and unbalanced evaluation metrics, such as precision, recall, overall accuracy, f1score, Jaccard index or intersection over union (IoU) [16] and kappa coefficient [17], are implemented.…”
Section: Introductionmentioning
confidence: 99%